2013
DOI: 10.4172/2155-6156.s6-006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orally Administered Microencapsulated FA-Producing L. fermentum on Markers of Metabolic Syndrome: An In Vivo Analysis

Abstract: Ferulic Acid (FA) is a natural phenolic acid produced by a number of lactic acid bacteria. FA has a number of beneficial properties, including: antioxidant activity, anti-tumorigenic properties and cholesterol-lowering capabilities. Our group has previously screened lactobacilli for FA production, and selected L. fermentum ATCC 11976 (L.f. 11976) as one of the best producers. Alginate-polylysine-alginate (APA) microencapsulation has proven successful for the oral delivery of this strain to the colon, where pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Preliminary data from two pilot non-randomized studies suggest that probiotics may be well-tolerated, may improve conventional liver function tests, and may decrease markers of lipid peroxidation. This probiotic formulation has also shown potential as a therapeutic for metabolic syndrome [45]. The positive effects of the microencapsulated L. fermentum ATCC 11976 formulation treatment on liver tests, histopathology and on parameters of pathological events related to NAFLD indicate its as a complementary therapeutic approach in fatty-liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data from two pilot non-randomized studies suggest that probiotics may be well-tolerated, may improve conventional liver function tests, and may decrease markers of lipid peroxidation. This probiotic formulation has also shown potential as a therapeutic for metabolic syndrome [45]. The positive effects of the microencapsulated L. fermentum ATCC 11976 formulation treatment on liver tests, histopathology and on parameters of pathological events related to NAFLD indicate its as a complementary therapeutic approach in fatty-liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we showed the ability of CRL1446 strain to reduce cholesterol levels independently of the diet administered or the matrix used to carry the probiotic in an obesity mice model. Also, Bhathena et al reported that the feruloyl esterase producing Limosilactobacillus fermentum LF11976 decreased serum lipids in hypercholesterolemic hamsters ( 48 ). Feruloyl esterases are enzymes responsible for cleaving insoluble wall-bound hydroxycinnamates, releasing ferulic acid (among other hydroxycinnamic acids) from plant matrixes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that CRL1446 has been shown to have a high feruloyl esterase activity (Abeijón Mukdsi et al, 2012) and could probably be the mechanism of action by which this strain exerts its hypocholesterolemic effect, in addition to the modifications that induces on the gut microbiota. In concordance, Bhathena et al reported that the feruloyl esterase producing strain, L. fermentum LF11976, decreased serum lipids in hypercholesterolemic hamsters (Bhathena, 2013). This assertion is based on the fact that the ferulic acid has hypocholesterolemic properties, since it can inhibit hydroxymethylglutaryl CoA reductase (a limiting enzyme in the biosynthesis of cholesterol) and cholesterol acyltransferase (enzyme that esterifies cholesterol in the tissues, mainly in the liver), and can increase the excretion of acid sterols (Balasubashini, Rukkumani, & Menon, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%